2014
DOI: 10.1007/s00198-014-2855-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on neuroplasticity in older adults: a double-blinded, placebo-controlled randomised trial

Abstract: Daily supplementation with 2,000 IU vitamin D3 for 10 weeks had no significant effect on neuroplasticity compared to placebo, but the finding that vitamin D treatment alone was associated with a decrease in corticospinal excitability and intracortical inhibition warrants further investigation as this suggests that it may improve the efficacy of neural transmission within the corticospinal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 35 publications
2
41
1
Order By: Relevance
“…This is in line with previous studies that found associations of BDNF and vitamin D or vitamin D supplementation with depression but reported no interactions between the measures [64, 65]. In summary, our hypothesis of an interaction between vitamin D and BDNF with obesity was not confirmed.…”
Section: Discussioncontrasting
confidence: 43%
“…This is in line with previous studies that found associations of BDNF and vitamin D or vitamin D supplementation with depression but reported no interactions between the measures [64, 65]. In summary, our hypothesis of an interaction between vitamin D and BDNF with obesity was not confirmed.…”
Section: Discussioncontrasting
confidence: 43%
“…Both season and latitude can be important covariates as a result of internal vitamin D production by ultraviolet‐B radiation . The season of blood withdrawal was not stated in six of the 15 studies and the geographic latitude was stated in three . Other covariates of vitamin D status (body mass index, ethnicity, smoking) were usually not considered specifically.…”
Section: Resultsmentioning
confidence: 99%
“…37 What is more, vitamin D affects neuroplasiticity, a process via which neural synapses and pathways are adapted to the needs of environmental and behavioral demands, adjusting the brain to noxious stimuli diseases or environmental cues. 38,39 Moreover, vitamin D affects GABAergic neurons in the motor cortex, 40 GABAergic function being the principal "brake" within the brain affecting muscle relaxation via the corticospinal neurons. 41 of particular note, GABAergic, serotonin and dopamine neurons are crucial in muscular coordination and the avoidance of central fatigue, 42 a high ratio of serotonin to dopamine positively impacting exercise performance because of serotonin's effect on the general feeling of tiredness and the perceptions of effort.…”
Section: Effects Of Vitamin D On the Nervous Systemmentioning
confidence: 99%